Rewinding of 3 Phase Induction Motor Double Speed - Linda Sartika; Abdul Muis Prasetia; Boby Setiawan; Tri Widodo (Fakultas Teknik Universitas Bhayangkara, 2024)
A double-speed motor is a type of asynchronous AC motor designed with two or more windings. The presence of two separate windings causes three-phase double-speed motors to have a significantly larger physical size compared to three-phase single-speed motors of the same power rating. Numerous studies have investigated the impact of the rewinding process on the efficiency of single-speed induction motors. However, limited attention has been given to double-speed induction motors. Addressing this research gap, the present study focuses on two primary objectives: first, to analyze the impact of rewinding on the performance characteristics of double-speed induction motors; and second, to evaluate the operational performance of these motors after undergoing the rewinding process. In this study, the rewinding process utilized copper wire with a diameter of 0.50 mm, wound using a mold to create a total of 52 windings. Performance testing revealed the following results: under no-load conditions with slow rotation, the motor exhibited a current of 1.3 A, a frequency of 50.45 Hz, a power factor (cos φ) of 0.86, and a speed of 1515 RPM. When a load was applied under fast rotation, the motor demonstrated a current of 1.9 A, a frequency of 50.29 Hz, a power factor (cos φ) of 0.997, and a speed of 2949 RPM. The experimental results showed minimal variation in current and frequency between loaded and unloaded conditions, with significant differences primarily observed in rotational speed between slow and fast modes. This behavior is characteristic of double-speed motors, which are capable of operating at two distinct speeds. In fast rotation mode, the speed can reach approximately twice that of slow rotation, highlighting the design's capability to adapt to varying operational demands.